Preliminary investigation on free-living marine nematode community biodiversity in coastal water of Ba Ria - Vung Tau province - Minh Thao, Hoang Thi; Huyen, Nguyen Thanh; Duong, Nguyen Anh; Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
The community structure, diversity and distribution of free-living marine nematodes were investigated the first time in the coastal zone of Ba Ria - Vung Tau province during 2006. The chemical and environmental parameters of surface water were measured as DO, pH, To, and NTU (turbidity). pH value fluctuated from 7.5 to 7.9; DO concentration was comparatively small and its value was lowest at the station VT 18 (4.5 mg/L) and highest at the station VT20 (7.9 mg/L). The turbidity value was low and fluctuated from 2NTU (VT7, VT20) to 12 NTU (VT16). The individual density of nematodes per 10 cm2 sediment in most sampling stations was high, its individuals fluctuated from 796,7 ± 40 at station VT15 to 8168.0 ± 70 at station VT10. Only at the station VT17 the density of individuals was recognized with a low value (404 inds/10cm2). Decreasing individual of nematode community at the station VT17 could be explained by a strong disturbed process of botton sediment. In total, there are 77 marine nematode species belong to 21 families of 7 orders were found. Most common predominant nematode species in all investigated stations were recognized as Pseudochromadora sp.2 (13.03%), Thalassironus sp. (7.07%), Spilophorella sp. (4.22%) and Paradontophora sp. (4%). Along 21 families were recorded, the family Desmodoridae dominated and occurred with the highest percentage (18.02%), following by family Comesomatidae 16.34%; family Chromadoridae 12.43%; and family Cyatholaimidae 12.15%. Otherwhile, there are 4 families that occured with under 1% per each family. They are Ceramonematidae (0.39%), Desmoscolecidae (0.36%), Thoracostomopsidae (0.11%) and Monhysteridae (0.07%). According to derived result, among 77 recognized marine free-living nematodes, species Pseudochromadora sp.2 comparatively distributed widely in coastal water area of Ba Ria-Vung Tau province. It was only absent at the following stations: VT11 and VT14. The second position occupied species component was Thalassironus, with 7.07% density, the third position was Paradontophora minor, with 4% density. Otherwhile, others species Paracanthoncus sp. was recognized with a high individuals density (9.71%) but it only distributed at one sampling station (VT11). The carnivorous and predatory nematode group (2A) dominated with 54.18 % of total species, The non selected deposit feeder group (1B) occured with 17.12%, the predator group (2B) occured with 14.92% and the selected deposit feeder group occured with only 13.76% of total species. The nematode biodiversity indices such as Shannon-Wiener index (H’) and Margalef index (d) were high at every studied station. H’ value fluctuated from 2,44 (VT11) to 4,54 (VT18). Besides, Magarlef index (d) was similar to Shannon-Wiener index (H’) value and it also fluctuated from 1,00 (VT11) to 4,16 (VT18). At stations VT18, VT10, VT7, VT17, VT15, VT21, VT20, VT8, VT16 and VT9, the values of Shannon-Wiener index (H’) fluctuated from 3.15 to 4.54, and according to Vietnam Water Standardization the biological water quality in that stations is non-polluted. At others stations like VT5, VT11 and VT 14, the values of Shannon - Wiener index (H’) were decreased (H’ = 2.44-2.62 and 2.94) and according to the score of the Vietnam Water Standardization, the water biological quality was shown a bad processing trend.